N-Glycome changes reflecting resistance to platinum-based chemotherapy in ovarian cancer - Zahradnikova, Martina; Ihnatova, Ivana; Lattova, Erika; Uhrik, Lukas; Stuchlikova, Eliska; Nenutil, Rudolf; Valik, Dalibor; Nalezinska, Monika; Chovanec, Josef; Zdrahal, Zbynek; Vojtesek, Borivoj; Hernychova, Lenka; et al. (Journal of proteomics, 2021)
A number of studies have reported aberrant glycosylation in connection with malignancy. Our investigation further expands on this topic through the examination of N-glycans, which could be associated with the resistance of advanced stage, high-grade non-mucinous ovarian cancer to platinum/taxane based chemotherapy. We used tissue samples of 83 ovarian cancer patients, randomly divided into two independent cohorts (basic and validation). Both groups involved either cases with/without postoperative tumor residue or the cases determined either resistant or sensitive to this chemotherapy. In the validation cohort, preoperative serum samples were also available. N-glycans released from tumors and sera were permethylated and analyzed by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). The MS analysis yielded a consecutive detection of 68 (tissue) and 63 (serum) N-glycan spectral signals. Eight of these were found to be differentially abundant in tissues of both independent cohorts including the cases with a postoperative cancer residue. One of these glycans was detected as differentially abundant in sera of the validation cohort. No statistically significant differences in intensities due to the same N-glycans were found in the cases without postoperative macroscopic residues in either the basic or validation cohort. From the biochemical point of view, the statistically significant N-glycans correspond to the structures carrying bisecting (terminal) GlcNAc residue and tetra-antennary structures with sialic acid and/or fucose residues. Among them, six tissue N-glycans could be considered potential markers connected with a resistance to chemotherapy in ovarian cancer patients. The prediction of primary resistance to standard chemotherapy may identify the group of patients suitable for alternative treatment strategies. SIGNIFICANCE: Drug resistance has become a major impediment to a successful treatment of patients with advanced ovarian cancer. The glycomic measurements related to cancer are becoming increasingly popular in identification of the key molecules as potential diagnostic and prognostic indicators. Our report deals with identification of differences in N-glycosylation of proteins in tissue and serum samples from the individuals showing sensitivity or resistance to platinum/taxane-based chemotherapy. The detection sensitivity to chemotherapy is vitally important for these patients.
Keywords: Female; glykosylace; polysacharidy; Ovarian Neoplasms; Platinum; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Humans; Polysaccharides; nádory vaječníků; ženské pohlaví; platina; spektrometrie hmotnostní - ionizace laserem za účasti matrice; lidé; Glycosylation